Division of labour in championing activities for technological innovations in Korea: patterns and performance consequences*. Issue 1 (2nd January 2016) - Kim, Youngbae; Shim, Duksup
Abstract : This study empirically examined the patterns of division of labour in championing activities for technological innovations in Korea, and their relationships with project and organisational complexity and the consequences of performance. Based on data from 88 new product development (NPD) projects in Korea, this study found that there were six different types of champion role structures: two solo champion structures, three dual champion structures, and one triple champion structure. This study examined the characteristics of key people who played three different champion roles in terms of education level, functional area, and hierarchical position in the organisation. It also revealed that organisational complexity led to specialisation of the champion role structure. Role specialisation in championing activities in general and the existence of an executive champion in particular had a significant impact on uncertainty reduction in terms of technology, market, resource acquisition, and organisation support, which in turn led to higher performances in the innovation project.